2019
DOI: 10.1093/mnras/stz746
|View full text |Cite
|
Sign up to set email alerts
|

Formation, vertex deviation, and age of the Milky Way’s bulge: input from a cosmological simulation with a late-forming bar

Abstract: We present the late-time evolution of m12m, a cosmological simulation of a Milky Way-like galaxy from the FIRE project. The simulation forms a bar after redshift z = 0.2. We show that the evolution of the model exhibits behaviours typical of kinematic fractionation, with a bar weaker in older populations, an X-shape traced by the younger, metal-rich populations and a prominent X-shape in the edge-on mean metallicity map. Because of the late formation of the bar in m12m, stars forming after 10 Gyr (z = 0.34) si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 97 publications
1
37
0
Order By: Relevance
“…the X-shape, is observed to be pronounced in metal-rich stars and weak or absent in the metal-poor ones (Ness et al 2012;Uttenthaler et al 2012;Rojas-Arriagada et al 2014). Secondly, but related to this, self-consistent chemo-hydrodynamical simulations (Debattista et al 2017(Debattista et al , 2019Athanassoula et al 2017) have predicted more pinched metallicity distributions than the density itself when viewed edge-on; this distribution has been confirmed in real galaxies (Gonzalez et al 2017). This trend is the equivalent of the metallicity dependence of the Xshape, generalised to external galaxies.…”
Section: Stellar Population Modellingmentioning
confidence: 54%
See 2 more Smart Citations
“…the X-shape, is observed to be pronounced in metal-rich stars and weak or absent in the metal-poor ones (Ness et al 2012;Uttenthaler et al 2012;Rojas-Arriagada et al 2014). Secondly, but related to this, self-consistent chemo-hydrodynamical simulations (Debattista et al 2017(Debattista et al , 2019Athanassoula et al 2017) have predicted more pinched metallicity distributions than the density itself when viewed edge-on; this distribution has been confirmed in real galaxies (Gonzalez et al 2017). This trend is the equivalent of the metallicity dependence of the Xshape, generalised to external galaxies.…”
Section: Stellar Population Modellingmentioning
confidence: 54%
“…The resulting X-shape is better traced by the metal-rich populations, as observed. They also showed that as a consequence the metallicity distribution is more peanut-shaped than the density itself (see also Athanassoula et al 2017;Buck et al 2018;Debattista et al 2019). Such a metallicity distribution has been confirmed in the edge-on galaxy NGC 4710, which hosts a B/P bulge (Gonzalez et al 2017).…”
Section: Insights From Bulge Chemistrymentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, none of the galaxies here exhibit the ring structures, presumed to be long-lived, seen by studies of the central regions of other spiral galaxies and the MW CMZ (Kormendy & Kennicutt 2004;Molinari et al 2011). We note the lack of strong bars in the centers of any of these FIRE galaxies at this time (m12m did develop a strong bar around z ≈ 0.2, but it does not survive to z = 0; Debattista et al 2019); without the presence of bars in these simulations at z = 0, we cannot speak to the dynamical importance of bars in producing central galactic environments similar to the MW CMZ. Other work has highlighted the potential impacts of bars in funneling gas core-ward and forming rings (Sormani et al 2015(Sormani et al , 2018.…”
Section: Two Morphological Classes Of Fire-cmzsmentioning
confidence: 46%
“…In many cases, authors assume a certain initial metallicity distribution and test the impact of the further secular evolution (e.g., Martel et al 2013;Martinez-Valpuesta & Gerhard 2013;Di Matteo et al 2013). The alternative approach is to trace stellar populations in hydrodynamical simulations with star formation and feedback (e.g., Grand et al 2016;Debattista et al 2017Debattista et al , 2019Tissera et al 2016Tissera et al , 2017Tissera et al , 2019Taylor & Kobayashi 2017).…”
Section: Origins Of the Spatial Trendsmentioning
confidence: 99%